1991
DOI: 10.1111/j.1476-5381.1991.tb12159.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N‐iminoethyl‐l‐ornithine as an irreversible inhibitor of nitric oxide synthase in phagocytic cells

Abstract: 1 The synthesis of nitric oxide (NO) from L-arginine by rat peritoneal neutrophils (PMN) and the murine macrophage cell-line J774 and the inhibition of this synthesis by N-iminoethyl-L-ornithine (L-NIO), NG-monomethyl-L-arginine (L-NMMA), N0-nitro-L-arginine (L-NNA) and its methyl ester (L-NAME) were investigated. 2 L-NIO was the most potent inhibitor in both types of cells while L-NMMA was less active. L-NNA and L-NAME had no significant effect in PMN and L-NNA produced only approximately 40% inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
0
3

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(154 citation statements)
references
References 17 publications
7
144
0
3
Order By: Relevance
“…Differences in the rank order potency of inhibitors of iNOS in J774 cells have been reported and McCall et al (8) hypothesized that these differences may reflect uptake of NOS inhibitors by different transport systems. Our findings have confirmed this hypothesis and identified system y + as a potential target for inhibitors of iNOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the rank order potency of inhibitors of iNOS in J774 cells have been reported and McCall et al (8) hypothesized that these differences may reflect uptake of NOS inhibitors by different transport systems. Our findings have confirmed this hypothesis and identified system y + as a potential target for inhibitors of iNOS.…”
Section: Discussionmentioning
confidence: 99%
“…N G -derivatized analogues of L-arginine are potent inhibitors of iNOS, and their rank order of potency has been attributed to different NOS isoforms and/or their differential rates of cellular uptake (7,8). In this context, we reported previously that N G -monomethyl-L-arginine (L-…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…L-Arginine analogs in conjunction with spectroscopic studies to determine the factors contributing to the Arg-NOS interaction yielded conflicting results. Some reports suggested that positive charge is required for the tight binding of L-Arg to NOS (33,34). Others showed that positive charge may not be critical for the Arg-NOS interaction (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In the first set of experiments, conditioned medium from unstimulated cells and cells treated with LPS (1000 ng/ml) and IFN-␥ (100 U/ml) was collected. Duplicate preparations of cells were treated with either the NO donor S-nitroso-Nacetyl-D,L-penicillamine (SNAP; Alexis) or L-N 5 -(1-iminoethyl)-ornithine (L-NIO; 80 M; Alexis), a selective iNOS inhibitor to block production of NO by these cells (21). Thus, exogenous NO was added to cells from non-OVA-treated mice through application of SNAP to approximate the NO production of cells from OVA-treated mice.…”
Section: Bal Cell Culturementioning
confidence: 99%